Probiotic as a bioactive ingredient in functional foods - Bednarek, Jadwiga Janina (Journal of Education, Health and Sport, 2018)
Consuming fermented milk drinks dates back to ancient times. Probiotics are one of the bioactive components that decide to give the food product the title of functional food. The viability of probiotic bacteria throughout the product’s lifecycle depends on the pH, storage temperature and quality of the constituents of the basic product. Therefore, strains that are a functional component added to foods must additionally meet technological requirements. The first products in the form of fermented beverages containing the Lactobacillus acidophilus intestinal strain were produced by the industry in the second and third decade of the 20th century. Food products are a more effective carrier of probiotic bacteria than pharmaceutical preparations. Often the name "probiotic product" does not mean a cause and effect relationship between a food product and the human body, but only testifies to the presence of a probiotic in its composition and mainly serves marketing purposes.